Calculations of rental incomes per townland for the Ormond estate, with a summary of purchase figure calculations and a summary of the findings, - Irish Land Commission (1903)
Includes an estimated price that Ormond’s properties in each townland would fetch if sold under the terms of the proposed land bill. With summaries of the value of holdings in Co. Kilkenny and Co. Tipperary.